A Modified Scrotoplasty for Treating Severe Penoscrotal Webbing in Children - Li, Yuan; Zhu, Xiaoyu; Feng, Dongchuan; Gong, Jinchao; Sun, Guangyao; Zhang, Xilun; Hu, Dianhe; Sha, Suoyou; Han, Tao (Frontiers in Pediatrics, 2020)
To compare a novel modified W-incision scrotoplasty (MWS) operation method with the conventional V-Y scrotoplasty for treatment of severe penoscrotal webbing (PSW) in children a retrospective study was conducted on 26 children. Circumcision combined with modified scrotoplasty was used to repair the webbed penis and phimosis of children and another 32 patients undergoing V-Y scrotoplasty served as the control group. There was a statistically significant difference of angle improvements of penis and scrotum in a horizontal position (-66 ± 10; -57 ± 6, P < 0.001) and the parent satisfaction score (Five Likert Scale) (4.7 ± 0.56; 3.8 ± 0.47, P < 0.001) between the two groups. All 26 children who underwent MWS presented with no serious postoperative complications, and there was no significant difference in surgical complications compared to children treated with V-Y scrotoplasty.